Chronic Ethanol Exposure Effects on Vitamin D Levels among Subjects with Alcohol Use Disorder - Olalekan Ogunsakin; Tete Hottor; Ashish Mehta; Maureen Lichtveld; Michael McCaskill (SAGE Publishing, 2016)
Vitamin D has been previously recognized to play important roles in human immune system and function. In the pulmonary system, vitamin D regulates the function of antimicrobial peptides, especially cathelicidin/LL-37. Human cathelicidin/LL-37 is a bactericidal, bacteriostatic, and antiviral endogenous peptide with protective immune functions. Chronic exposure to excessive alcohol has the potential to reduce levels of vitamin D (inactive vitamin D [25(OH)D 3 ] and active vitamin D [1, 25(OH) 2 D 3 ]) and leads to downregulation of cathelicidin/LL-37. Alcohol-mediated reduction of LL-37 may be partly responsible for increased incidence of more frequent and severe respiratory infections among subjects with alcohol use disorder (AUD). The objective of this study was to investigate the mechanisms by which alcohol exerts its influence on vitamin D metabolism. In addition, the aim was to establish associations between chronic alcohol exposures, levels of pulmonary vitamin D, and cathelicidin/LL-37 using broncho-alveolar lavage fluid samples of subjects with AUD and healthy controls. Findings from the experiment showed that levels of inactive vitamin D (25(OH)D 3 ), active vitamin D (1, 25(OH) 2 D 3 ), cathelicidin/LL-37, and CYP27B1 proteins were significantly reduced ( P < 0.05) when compared with the matched healthy control group. However, CYP2E1 was elevated in all the samples examined. Chronic exposure to alcohol has the potential to reduce the levels of pulmonary vitamin D and results in subsequent downregulation of the antimicrobial peptide, LL-37, in the human pulmonary system.